In utero Exposure to Anesthetics Alters Neuronal Migration Pattern in Developing Cerebral Cortex and Causes Postnatal Behavioral Deficits in Rats. (11th April 2019) - Gluncic, V; Moric, M; Chu, Y; Hanko, V; Li, J; Lukić, I K; Lukić, A; Edassery, S L; Kroin, J S; Persons, A L; Perry, P; Kelly, L; et al.
Abstract: During fetal development, cerebral cortical neurons are generated in the proliferative zone along the ventricles and then migrate to their final positions. To examine the impact of in utero exposure to anesthetics on neuronal migration, we injected pregnant rats with bromodeoxyuridine to label fetal neurons generated at embryonic Day (E) 17 and then randomized these rats to 9 different groups receiving 3 different means of anesthesia (oxygen/control, propofol, isoflurane) for 3 exposure durations (20, 50, 120 min). Histological analysis of brains from 54 pups revealed that significant number of neurons in anesthetized animals failed to acquire their correct cortical position and remained dispersed within inappropriate cortical layers and/or adjacent white matter. Behavioral testing of 86 littermates pointed to abnormalities that correspond to the aberrations in the brain areas that are specifically developing during the E17. In the second set of experiments, fetal brains exposed to isoflurane at E16 had diminished expression of the reelin and glutamic acid decarboxylase 67, proteins critical for neuronal migration. Together, these results call for cautious use of anesthetics during the neuronal migration period in pregnancy and more comprehensive investigation of neurodevelopmental consequences for the fetus and possible consequences later in life.